SINERGITAS PRINSIP BHINEKA TUNGGAL IKA DENGAN PRINSIP PLURALISME HUKUM - Benyamin Tungga (Jurnal Aktual Justice, 2019)
In fact, bineka tunggal ika is a form of pluralism in one culture, ethnicity, religion, and others in one place, namely the state with Pancasila principles and the 1945 Constitution. Whereas the principle of legal pluralism is a situation where one or more legal systems apply at a time and place the same one. The purpose of this paper is to explain how the synergy of the single eka bineka principle with the principle of legal pluralism. The single unity principle that is manifested in the life of nation and state, one form of its implementation is explained in the Indonesian archipelago, a way of looking at the Indonesian people about themselves and their surrounding environment based on national ideas based on Pancasila and the 1945 Constitution. Using the basis of Pancasila and the 1945 Constitution as part of legal sources. Thus it can be concluded that there is a synergy between the single bineka ika principle and the principle of legal pluralism in the basic model of the Indonesian unitary republic which lies in the source of all sources of law, namely Pancasila and the 1945 Constitution.